LINGUO-CULTURAL COMPETENCE AND ITS ROLE IN PROFESSIONAL FORMATION OF FUTURE SPECIALISTS OF EDUCATIONAL INSTITUTIONS - Inna D. Davydchenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The article discusses topical issues of the formation of linguo-cultural competence of future specialists of educational institutions. We believe that linguo-culturological competence is of great importance for pedagogical and scientific-pedagogical workers, which ensures the effectiveness of their fulfillment of basic professional tasks. Since linguo-cultural competence is an integrative multidimensional innovation that does not arise spontaneously, a purposeful formation is needed, which should begin in higher educational institutions, where future specialists of educational institutions are trained. The National Doctrine of Education Development of Ukraine in the XXI century stated that the main aim of the Ukrainian education system is to create conditions for the development and self-realization of each individual, to ensure high quality education for graduates of high pedagogical institutions. The conceptual model of high education in Ukraine has actualized the tasks of training a new exemplar professional – an active person with critical thinking and a creative approach to solving problems, ready for self-education and self-development, for effective interaction with the environment. In our opinion, the linguistic and cultural competence of higher education students should be represented by linguistic and cultural components. The purpose of our research is to examine linguocultural competence and its role in the professional development of future specialists in educational institutions. The methodology is based on the general principles of philosophy, basic modern provisions of pedagogical science, psychology and reflects the relationship of methodological approaches to the study of the process of organizing the educational process. Methods of linguocultural competence: a diachronic method based on a comparative analysis of various linguocultural units in time; synchronous method, compares simultaneously existing linguocultural units; structural and functional method, which involves the distribution of a cultural object into parts and the identification of connections between parts; a historical and genetic method focused on the study of a linguoculturological fact from the point of view of its occurrence, the development of further destiny; a typological method designed to identify the typological proximity of various linguoculturological units of the historical and cultural process; the comparative-historical method is based on the comparison of original linguoculturological units in time and insight into their essence. These methods enter into mutually complementary relationships, special conjugation with various cognitive principles, methods of analysis, allows cultural linguistics to explore its complex object - the interaction of language and culture. Scientific novelty. By the linguistic and cultural competence of future specialists of educational institutions we mean the quality of language personality, expressed by linguistic and cultural knowledge, special skills and personal qualities, which promotes integration into world culture and participation in intercultural communication, avoiding interlingual and intercultural conflicts. It is impossible to learn culture without knowing of the relevant language, which is not only a material component of culture, thanks to which communicative tasks are solved, but also a penetration attempt to the people’s mode of thinking, an attempt to look at the world through the culture. Thus, we determine the content and structure of linguistic and cultural competence according to the nature and essence of cultural linguistics, which is the theoretical basis of our research. A special subject frame in the structure of linguistic and cultural competence is considered by the components of the structure of linguistic and cultural competence of future specialists of educational institutions, which should be supplemented by professional and pedagogical training that will provide quality implementation of professional competence. In summary, linguistic and cultural competence as an integrative quality of future specialists’ personality of educational institutions should be formed through a system of didactic material, using cultural and educational potentials of Ukrainian, with obligatory coverage of its close connection with history, spiritual culture, mentality of the people, knowledge its history and place among other languages of the world. This competence involves the development of the following abilities in the personality: a) the ability to perceive language as a cultural phenomenon, as a cultural and historical environment that turns into the history, culture, people’s customs; b) the ability to acquire the culture of communication, or language culture; runs of linguistic, communicative and culturological competence; c) the ability to sense language in its aesthetic function – as a means of creating the art of speech.